Avaliação de biomarcadores por meio de espectroscopia ATR-FTIR em trabalhadores em turnos e a sua associação com o cronotipo e duração do sono - Vieira, Talles Fillipe Barcelos (2022)
The demand for employees available 24/7 can cause circadian misalignment and sleep deprivation, which has been linked to the development of metabolic diseases. In this scenario, ATR-FTIR spectroscopy might be a potential tool for detecting initial evidence, such as molecular spectrum alterations, of future metabolic outcomes. The aim of this study was to investigate the ATR-FTIR infrared spectrum of shift workers’ serum in order to identify wavenumbers capable of differentiating day and night workers, and verify the associations between these regions and workers’ chronotype and sleep duration. This study was performed with 38 male workers of which 19 worked the night shift and 19 worked the day shift. The wavenumbers 1522 cm-¹, 1636 cm-¹, related to proteins, and the bands 2871 cm-¹, 2927 cm-¹, 2955 cm-¹, associated to lipids, significantly differed day from night workers and showed higher absorption in night workers’ serum. The Generalized Linear Model (GLzM) was used to identify interactions between theses wavenumbers, chronotype and sleep duration, showing that day workers with evening tendency were associated to an increase in the bands related to lipids, while no interaction with workers’s sleep duration was found. Therefore, our result demonstrates that night shift and chronotype might be related to higher absorbance in spectral regions related to lipids and proteins. We concluded that the ATR-FTIR seems to be useful monitoring shift workers’ health.